Postoperative assessment of cervical muscle morphology, strength, and functional outcomes in patients with degenerative cervical myelopathy - Naghdi, Neda; Weber, Michael H.; Fortin, Maryse (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionDecompressive surgery is considered a practical option for patients with progressive degenerative cervical myelopathy (DCM), nearly 40% of patients with moderate and severe DCM report partial recovery post-surgery (e.g., <50% improvement).Research questionTo examine the impact of decompression surgery on cervical muscle morphology and strength in DCM patients and the relationship between preoperative muscle conditions and postoperative outcomes.Material and methodsA total of 10 DCM patients underwent surgery and were followed for 2 years. Among 10 patients, 7 underwent posterior fusion surgery, and 3 underwent anterior cervical discectomy and fusion (ACDF). Cervical muscle strength and MRI measurements were taken before and after surgery. Metrics included cross-sectional area (CSA), functional CSA (FCSA), fatty infiltration, and asymmetry of multifidus and semispinalis cervicis (MF + Scer) muscles. Functional outcomes were assessed using the modified Japanese Orthopedic Association, Neck Disability Index, and SF−12 health survey post-surgery.ResultsNo significant differences in isometric cervical muscle strength were found between the ACDF and posterior fusion groups at the two-year follow-up. Posterior fusion resulted in decreased MF + Scer muscle CSA (p = 0.01), FCSA (p = 0.027), and increased asymmetry (p = 0.003). The entire cervical extensor muscle CSA also decreased (p < 0.03) with posterior fusion. ACDF led to decreased CSA (p = 0.001) and FCSA (p < 0.001) of all cervical muscles. No significant correlations were observed between pre-surgery muscle measures and functional score changes in posterior fusion.ConclusionContrary to our hypothesis, cervical muscle strength did not improve two years post-surgery in either surgical group. Additionally, no significant correlations were observed between pre-surgical muscle strength or fat infiltration and postoperative functional outcomes. Posterior fusion surgery had a more pronounced effect on cervical musculature compared to ACDF, with greater reductions in muscle CSA and increases in asymmetry.